Role of Foreign Investment and External Debt in Determination of Exchange Rate - Basit, Abdul; Ansari, Ishaque Ahmed (Quarterly Journal of Econometrics Research, 2015)
The purpose of study is to observe importance and impact of the external debt and foreign investment in exchange rate of Pakistan. Ordinary Least Square and Exact Maximum Likelihood methods have been used for estimating the models. Cost of foreign debt has the significant relationship with the exchange rate and it has inverse relationship. Cost of foreign investment has also significant relationship with the exchange rate of Pakistan. The direction of relationship is same in both estimation methods but the significance level of the variables are different in both cases. It is also observed that the first lagged of exchange rate is also playing an important role for determination of exchange rate model.